Severe community-acquired pneumonia caused by Chlamydia pecorum. (November 2022) - Cao, Lizhen; He, Lin; Wang, Siyuan; Xu, Lianjie; Zhuang, Shifang
HIGHLIGHTS: We report the first case of human Chlamydia pecorum pneumonia . C. pecorum infection was identified by metagenomic next-generation sequencing and complement fixation test. The patient was a farmer with diabetes and had close contact with sheep. High fever, dry cough, and pulmonary consolidation are the main features. Abstract: Chlamydia pecorum is a zoonotic pathogen. Here, we report the first case of human infection with C. pecorum . A man aged 51 years with high fever and dry cough was diagnosed with severe community-acquired pneumonia and respiratory failure. C. pecorum was found responsible for the infection, which was detected from bronchoalveolar lavage fluid through metagenomic next-generation sequencing. C. pecorum infection was further identified by quantitative polymerase chain reaction and complement fixation test. The patient's condition improved rapidly after targeted treatment. He was a farmer with diabetes mellitus and had a history of close contact with sheep, which might result in C. pecorum infection. Our report could provide a direction for the diagnosis and treatment of human C. pecorum pneumonia .